N-Glycosylation of trpm8 Ion Channels Modulates Temperature Sensitivity of Cold Thermoreceptor Neurons - Madrid-Montecinos, R; Pertusa-Pastor, M (2012)
TRPM8 is a member of the transient receptor potential ion channel superfamily, which is expressed in sensory neurons and is activated by cold and cooling compounds, such as menthol. Activation of TRPM8 by agonists takes place through shifts in its voltage activation curve, allowing channel opening at physiological membrane potentials. Here, we studied the role of the N-glycosylation occurring at the pore loop of TRPM8 on the function of the channel. Using heterologous expression of recombinant channels in HEK293 cells we found that the unglycosylated TRPM8 mutant (N934Q) displays marked functional differences compared with the wild type channel. These differences include a shift in the threshold of temperature activation and a reduced response to menthol and cold stimuli. Biophysical analysis indicated that these modifications are due to a shift in the voltage dependence of TRPM8 activation toward more positive potentials. By using tunicamycin, a drug that prevents N-glycosylation of proteins, we also evaluated the effect of the N-glycosylation on the responses of trigeminal sensory neurons expressing TRPM8. These experiments showed that the lack of N-glycosylation affects the function of native TRPM8 ion channels in a similar way to heterologously expressed ones, causing an important shift of the temperature threshold of cold-sensitive thermoreceptor neurons. Altogether, these results indicate that post-translational modification of TRPM8 is an important mechanism modulating cold thermoreceptor function, explaining the marked differences in temperature sensitivity observed between recombinant and native TRPM8 ion channels. © 2012 by The American Society for Biochemistry and Molecular Biology, Inc.